Hepatic Immunosuppressive Effects of Systemically-Administered Novel Dextran-Methylprednisolone Prodrugs with Peptide Linkers in Rats - Shaik, Imam H. (2012)
The hepatic immunosuppressive activities of two novel dextran prodrugs of methylprednisolone (MP) containing one (DMP1) or five (DMP5) amino acids as linkers were studied in rats. At various times (0–2 weeks) after intravenous administration of single 5-mg/kg (MP equivalent) doses of each prodrug or MP succinate (MPS), livers were isolated and immunologically stimulated ex vivo with lipopolysaccharide. The concentrations of tumor necrosis factor (TNF)-α in the outlet perfusate were then quantitated to assess immune response. Additionally, the concentrations of DMP1, DMP5, and/or MP were measured in the liver. MPS, DMP5, or DMP1 injections caused a maximum of 48.9%, 63.5%, or 85.7% decrease in the TNF-α secretion into the perfusate, with the time above the 50% inhibitory effect being <5, <24, or 120 h, respectively. Additionally, the area under the effect-time curve for DMP1 was 11- or 4-fold higher than that after the administration of MPS or DMP5, respectively. Relatively high concentrations of DMP1 were present in the liver even at the last sampling time of two weeks. These data suggest that a single intravenous dose of DMP1 produces an intense and sustained immunosuppression in the liver for a relatively long time, which may be useful in liver transplantation.